Preliminary interface characterisation of Cold Sprayed copper on aluminium - Ceguerra, A; Moody, M; Cairney, J; Jahedi, M; Ringer, S (2007)
Cold Spray technology is a novel coating technique where a jet stream of small powder particles (1 - 50 μm) is accelerated to supersonic speeds (300 - 1200 m/s) by a compressed gas towards a substrate, and a strong metallurgical bond is formed between the particles and the substrate. However, being a relatively new technique, the bonding mechanism between particles and substrate is not well understood. In this preliminary study, the interface between Cu particles that were Cold Sprayed and an Al substrate is investigated, using an Optical Microscope, a Scanning Electron Microscope (SEM), and a Transmission Electron Microscope (TEM). © Institute of Materials Engineering Australasia Ltd.